The ultrasound-based cardiac output monitoring is a useful tool to define baseline hemodynamic parameters in healthy permanent residents at high altitude: results of a monocentric pilot study - Viruez-Soto, Antonio; Molano-Franco, Daniel; Merino-Luna, Alfredo; Bairam, Aida; Aliaga-Raduán, Fernanda; Sanchez, Lida; Arias-Reyes, Christian; Soliz, Jorge (Frontiers in Physiology, 2024)
Previous studies on the cardiac data of healthy permanent residents living in high-altitude regions such as Tibet and the Andes have yielded inconsistent findings and significant disparities. These discrepancies can be mainly attributed to the invasive methods conventionally used for parameter evaluation. However, with the introduction of cutting-edge ultrasound technology, there is now an innovative approach to addressing and reconciling these variations. In this pilot study, we employed an ultrasound-based cardiac output monitoring (USCOM) device to evaluate cardiac output and related hemodynamic variables in a group of 20 healthy high-altitude Andean residents (comprising 10 men and 10 women) aged between 26 and 35 years old. The monocentric study was carried out in La Paz, Bolivia, located between at an altitude of 3,600–4,000 m. A total of 60 hemodynamic measurements were evaluated, accounting for three technical replicates per subject. Our results showed strong intrasubject reproducibility and revealed important differences related to both sex and hemodynamic parameters in highlanders compared to individuals residing at sea level. We conclude that USCOM represents a highly reliable technology for performing hemodynamic measurements in high-altitude residents. Our preliminary findings underscore the need for larger studies, encompassing larger sample sizes, specifically tailored to gender considerations, and extendable to broader highland populations. These findings have special significant implications for the management of hemodynamics in intensive care and postoperative settings, warranting further comprehensive research efforts.